1976
DOI: 10.1007/bf00454854
|View full text |Cite
|
Sign up to set email alerts
|

The capacity of phototrophic sulfur bacterium Thiocapsa roseopersicina for chemosynthesis

Abstract: Purple sulfur bacterium Thiocapsa roseopersicina strain BBS requiring vitamin B12 may grow in the dark in media containing no other organic compounds. Under such conditions the cells oxidize sulfide and thiosulfate with the use of O2 and assimilate carbon dioxide. After 10--30s assimilation of NaH14CO3 about 60% of radioactivity is found in phosphorylated compounds characteristic for the reductive pentose phosphate cycle. The possibility of the function of this cycle in the dark in the presence of O2 is confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 17 publications
0
30
0
1
Order By: Relevance
“…The in vivo absorption spectra of both strains indicate the presence of bacteriochlorophyll a (Fig. 2) (Kondratieva et al, 1976;Puchkova et al, 2000;Herbert et al, 2005). Both strains are catalase-positive, utilize many organic compounds phototrophically, and also grow aerobically in the dark with malate (strain LQ17) or fructose (strain KS1) as electron and carbon source.…”
Section: Discussionmentioning
confidence: 91%
“…The in vivo absorption spectra of both strains indicate the presence of bacteriochlorophyll a (Fig. 2) (Kondratieva et al, 1976;Puchkova et al, 2000;Herbert et al, 2005). Both strains are catalase-positive, utilize many organic compounds phototrophically, and also grow aerobically in the dark with malate (strain LQ17) or fructose (strain KS1) as electron and carbon source.…”
Section: Discussionmentioning
confidence: 91%
“…For example, certain Chromatiaceae, including species of Allochromatium, Thiocystis, Amoebobacter, and Thiocapsa, can grow in darkness as either chemoorganotrophs or chemolithotrophs when the oxygen concentration is signifi cantly reduced [microaerobic growth; Kämpf and Pfennig, 1980]. Thiocapsa roseopersicina and Thiocystis violacea are the most oxygen tolerant purple sulfur bacteria (Kondratieva et al, 1976;Kämpf and Pfennig, 1980); however, respiratory growth of these species is very slow compared with phototrophic growth. If one considers that dark growth of purple sulfur bacteria in nature puts them in direct competition with nonphototrophic bacteria as well as with purple nonsulfur bacteria, the ecological signifi cance of dark metabolism by purple sulfur bacteria is probably minor.…”
Section: A Purple Sulfur Bacteriamentioning
confidence: 99%
“…Batch culture experiments of Pfennig (1971), Bogorov (1974), Gorlenko (1974), Kondratieva et al (1976) and K/impf and Pfennig (1980Pfennig ( , 1986 revealed the capacity of Thiocapsa roseopersicina, Amoebobacter roseus, Thioc~,stis violacea, Chromatium vinosum, C. minus, C. violascens and C. gracile to grow in the dark by oxidizing reduced inorganic sulfur compounds with oxygen. In contrast, green sulfur bacteria did not grow chemotrophically (K/impf and Pfennig 1980).…”
mentioning
confidence: 99%
“…Under these conditions chemotrophically growing cells still contained photosynthetic pigments (Gorlenko 1974, Kondratieva et al 1976, K/impf and Pfennig 1986. Furthermore, growth of some strains under dark conditions continued for a limited period of time but ceased after repeated transfer into fresh culture medium (K/impf and Pfennig 1986).…”
mentioning
confidence: 99%